Temporal and spatial distribution of microplastics in the freshwater Atibaia river basin, Campinas-SP, Brazil - Glaucia Peregrina Olivatto; Romulo Augusto Ando; Rafaella Ferreira Fernandes; Ana Laura Athayde Lourenço; Adijailton José de Souza; Valdemar Luiz Tornisielo (Heliyon)
The contamination of surface waters by microplastics (MPs) is an emerging concern, due to their environmental impact and negative effects on biota. However, in recent years, although the occurrence of these pollutants has been widely reported in marine systems, studies on MPs in freshwater are still scarce in the literature, particularly in Southeastern Brazil. In this context, the current study aimed to provide unprecedented information on the abundance and spatial and temporal distribution of MPs in three sites located in the Atibaia river basin (Southeastern Brazil) - the main river, a tributary, and the discharge of effluent from a sewage treatment plant. Surface water was sampled in four sampling campaigns, two in wet season and two in dry season, between 2019 and 2020, at three sampling points. At each point, 200 L of water were collected with the aid of an aluminium bucket, followed by sieving in the field to isolate the particles between 100 μm and 5000 μm, using stainless steel sieves. Chemical identification of the polymer was performed by ATR-FTIR micro spectroscopy. The abundance of MPs in the water ranged from 188 to 533 items/m3. The water samples with the greatest MPs abundance corresponded to the sampling point that includes the receipt of domestic effluent treated by the local Sewage Treatment Station. The chemical identification of the polymers highlights polyester polyethylene terephthalate (PET), polyethylene (PE), polyvinyl chloride (PVC), and polypropylene (PP) as the most frequent, respectively. This study emphasizes the importance of discharged domestic effluents and rivers as MPs transport systems. Therefore, further studies should be carried out to identify the main sources and contribute to the gathering of information, aiming to mitigate the emission of this pollutant in aquatic systems.